A New Certificate Chemistry 6th Edition - Holderness: Lambert (Heinemann Secondary Education: usa, 1987)
A New Certificate Chemistry is known throughout the world as an invaluable resource for school chemistry courses, both in the classroom and in the laboratory.
Keywords: Chemistry - Text book